Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) (x+6)(3x-1)+x+6=0
⇔(x+6)(3x-1)+(x+6)=0
⇔(x+6)(3x-1+1)=0
⇔3x(x+6)=0
2) (x+4)(5x+9)-x-4=0
⇔(x+4)(5x+9)-(x+4)=0
⇔(x+4)(5x+9-1)=0
⇔(x+4)(5x+8)=0
3)(1-x)(5x+3)÷(3x-7)(x-1)
=\(\frac{\left(1-x\right)\left(5x+3\right)}{\left(3x-7\right)\left(x-1\right)}=\frac{\left(1-x\right)\left(5x+3\right)}{\left(7-3x\right)\left(1-x\right)}=\frac{\left(5x+3\right)}{\left(7-3x\right)}\)
Bài 1
1.(x-3)(x+2)-x(x-7)=15
\(\Leftrightarrow x^2+2x-3x-6-x^2+7x=15\)
\(\Leftrightarrow-6+6x=15\)
\(\Leftrightarrow6x=15+6\) =21
\(\Rightarrow x=\dfrac{21}{6}=3,5\)
2.(x-5)(x+5)+x(3-x)=20
\(\Leftrightarrow x^2-25+3x-x^2=20\)
\(\Leftrightarrow-25+3x=20\)
\(\Leftrightarrow3x=20+25=45\)
\(\Rightarrow x=\dfrac{45}{3}=15\)
3.(x-7)2-x(2+x)=-7
\(\Leftrightarrow x^2-14x+49-2x-x^2=-7\)
\(\Leftrightarrow-16x+49=-7\)
\(\Leftrightarrow-16x=-7-49=-56\)
\(\Rightarrow x=\dfrac{-56}{-16}=\dfrac{7}{2}=3,5\)
Tiếp bài 1
4.(x-4)2-(x+4)(x-4)=-16
\(\Leftrightarrow x^2-8x+16-x^2-16=-16\)
\(\Leftrightarrow-8x=-16\)
\(\Rightarrow x=\dfrac{-16}{-8}=2\)
5.(x-5)(x+5)-x(2-3x)=4x2-7
\(\Leftrightarrow x^2-25-2x+3x^2=4x^2-7\)
\(\Leftrightarrow4x^2-25-2x+3x^2=4x^2-7\)
\(\Leftrightarrow4x^2-4x^2-2x=-7+25\)
\(\Leftrightarrow-2x=18\)
\(\Rightarrow x=\dfrac{18}{-2}=-9\)
\(\frac{7-x}{2}+\frac{2}{3}.\left(x-7\right)\left(x-3\right)=0\)
\(\Leftrightarrow\frac{x-7}{-2}+\frac{2\left(x-7\right)}{3}\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-7\right)\left[\frac{-1}{2}+\frac{2}{3}\left(x-3\right)\right]=0\)
\(\Leftrightarrow\left(x-7\right)\left(\frac{-1}{2}+\frac{2x}{3}-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-7=0\\\frac{-1}{2}+\frac{2x}{3}-2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=7\\-\frac{5}{2}+\frac{2x}{3}=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=7\\\frac{2x}{3}=\frac{5}{2}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=7\\x=\frac{15}{4}\end{cases}}}\)